Preliminary Screening Of Subsurface Soils From Radionuclides And Metal Contaminated Area Of Orissa Coast - S.P.S.BISHT; B.PRAVEEN; AMRITA PANDA; SISIR DAS (International Journal of Pharma and Bio Sciences, 2011)
Radionuclides and metals have posed a great threat to the sustenance of life on earth. These are released by various anthropogenic activities and get accumulated without being eliminated. This environmental hazard can be alleviated by the microbes with the bioleaching property. The present study was designed to isolate microbes that help in the bioremediation of various metals and radionuclides from the sites of Indian Rare Earths Limited (IREL), Berhampur,Orissa. The isolated microbes Deinococcus radiodurans and Rhizopus have been shown to grow well in media supplemented with varied concentrations of different metals .Deinococcus radiodurans was found to be the toughest bacterium to tolerate the radiations and is utilized for in situ bioremediation of radioactive waste by producing higher amount of alkaline phosphatase enzyme and the only fungus Rhizopus studied in this work was helpful in uranium precipitation.